Bibliometric Analysis: Partnership in Achieving Competitive Advantage - Raja Ainaya Alfatiha; Arianis Chan; Anang Muftiadi (Politeknik Ganesha Medan, 2023)
The abstract The purpose of this research is to provide information from the results of identification and mapping of research around partnerships in achieving competitive advantage. The research method used is bibliometric analysis through articles in the Scopus database. The main procedure is to manually filter articles from search results to obtain relevant articles. The total number of articles obtained from the beginning of the 2000-2021 research year was 798 articles, after a screening process, 238 relevant articles were obtained. The results showed that the total publications from 2000-2021 experienced a fluctuating cycle, with the peak of the study occurring in 2020 with 22 articles. Then the countries that do the most research and the most in citations are the United States and the United Kingdom. Meanwhile, the mapping results using VOSviewer are obtained by four keyword clusters from previous research. The yellow color in the node indicates the development of the research topic.